Adult acute lymphoblastic leukemia in a resource-constrained setting: outcomes after expansion of genetic evaluation. Issue 1 (31st December 2022) - Silva, Wellington F.; Amano, Mariane T.; Perruso, Luiza L.; Cordeiro, Maria Gabriella; Kishimoto, Renata Kiyomi; de Medeiros Leal, Aline; Nardinelli, Luciana; Bendit, Israel; Velloso, Elvira DRP; Rego, Eduardo M.; Rocha, Vanderson
ABSTRACT: Acute lymphoblastic leukemia (ALL) is a challenging disease with a growing genetic landscape, even though there is substantial gap between developed and non-developed countries when it comes to availability of such new technologies. This manuscript reports a 5-year retrospective cohort of newly diagnosed ALL patients and their genetic findings and outcomes. An expanded genetic evaluation by using FISH and RT–PCR was implemented, aiming to identify Ph-like alterations. Patients were treated according to our local protocol, which allocated patients according to age and Philadelphia-chromosome status. A total of 104 patients was included, with median age of 37.5 years. Philadelphia chromosome was detected in 33 cases of B-lineage. Among 45 Ph-negative B-lineage, after excluding KMT2A or TCF3-PBX1 cases, we identified 9 cases with Ph-like fusion. Ph-positive and Ph-like patients had higher initial WBC ( p  = 0.06). Out of 104 cases, two cases did not start chemotherapy and an early death rate of 10.8% was found. Allogeneic transplantation was performed in 18 cases, being ten performed in first CR. Three-year overall survival (OS) and 3-year event-free survival were 42.8% and 30.8%, respectively. For patients treated with a pediatric regimen, 3-year OS was 52.5%. Extramedullary disease (HR 0.42) and platelet counts (HR 0.9) were independently associated with OS. We still face excessive non-relapse mortality that compromises our results. Alternative strategies implementing FISH and RT–PCR are feasible and able to identify Ph-like fusions. Delays in allogeneic transplantation, as well as the unavailability of new agents, impact long-term survival. Measures to decrease early infection are desirable.